EFFECT OF EMOTIONAL INTELLIGENCE, COMMITMENT, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. YEAKIN PLASTIC INDUSTRY BATAM. - Bangun Faozi; Ramon Zamora; Dini Anggraini (EQUILIBIRIA, 2017)
This study aims to determine the Effect of Emotional Intelligence, Commitment, And Job Satisfaction on Employee Performance at PT. Yeakin Plastic Industry Batam. Sampling technique used in this study is a saturated sampling, the sample number is same with the total population as 46 responded at QC department of PT. Yeakin Plastic Industry Batam. Types of data sources used are primary data, obtained from the respondents' answers on the questionnaire, and secondary data obtained from the data or documents the PT. Yeakin Plastic Industry Batam, as well as books and journals from previous research. Techniques of data retrieval that is by distributing questionnaires to 46 respondents, and documentation from the company is a brief history , organizational structure , employee data , and others. Data analysis method used is multiple linear regression analysis using SPSS 20 for Windows. The study states that ( 1 ) partially Emotional Intelligence positive and significant effect on the performance with significant score is 0,001 0,05 ( 2 ) Commitment positive and significant effect on the performance of employees with significant score is 0,007 0,05 ( 3 ) Job Satisfaction positive and significant effect on employee performance with significant score is 0,001 0,05 ( 4 ) Effect of Emotional Intelligence, Commitment, And Job Satisfaction positive and significant effect simultaneously on the performance of employees at PT. Yeakin Plastic Industry Batam with the significant score is 0,000 0,05 on the QC devision. With the value of adjusted R square of 0.545, in this case shows that the performance of employees affected by variables Emotional Intelligence, Commitment, And Job Satisfaction of 54.5 % . The remaining 45.5% is influenced by other variables which is not included in this research method. With multiple linear regression equation Y =  2,932 + 0,272 X1 + 0,313 X2 + 0,352 X3.